2012
DOI: 10.1080/17408989.2011.582491
|View full text |Cite
|
Sign up to set email alerts
|

Changes in teaching efficacy of pre-service teachers in physical education

Abstract: Background: The term teacher efficacy is defined as teachers' belief in their ability to significantly affect their pupils' learning. Studies in the physical education (PE) domain seeking sources of teaching efficacy reported on the links among external environmental factors, content knowledge, and 'learners' active engagement in learning, and the effect of these ties on teachers' efficacy. In the majority of the studies, self efficacy was assessed mostly on in-service experienced teachers. Purpose: to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 32 publications
(38 reference statements)
3
37
0
7
Order By: Relevance
“…De fato, cabe aos programas de formação inicial promover estratégias diversificadas que enfatizem a prática do ensino de professores em formação e ao longo da carreira 9,18,19 , em especial, práticas controladas que possam garantir alguma eficácia aos professores 31 , favorecendo a ampliação e a memorização de repertórios pessoais de êxitos sobre o ensino.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…De fato, cabe aos programas de formação inicial promover estratégias diversificadas que enfatizem a prática do ensino de professores em formação e ao longo da carreira 9,18,19 , em especial, práticas controladas que possam garantir alguma eficácia aos professores 31 , favorecendo a ampliação e a memorização de repertórios pessoais de êxitos sobre o ensino.…”
Section: Discussionunclassified
“…Assim, cabe aos professores supervisores ou orientadores de estágio a mediação entre a teoria e a prática, de modo a facilitar o aprendizado dos universitários 17 . No âmbito da Educação Física, estudos recentes têm buscado investigar as crenças de autoeficácia de universitários em Educação Física 18 ; avaliar a eficácia no ensino de universitários ao longo da formação inicial para determinar se sofre alguma alteração durante os anos de formação 19 ; determinar o nível de autoeficácia entre os alunos que estudam desporto e Educação Física para ensinar os alunos com deficiência intelectual 20 ; medir e analisar a autoeficácia e suas origens para o ensino da Educação Física 21 ; identificar as relações do constructo da autoeficácia com os aspectos da formação inicial 22 ; e compreender como se constituem as crenças de autoeficácia para o ensino da Educação Física 5 . Embora se verifique um incremento importante nos estudos sobre a temática da autoeficácia, acredita-se que a realização de estudos que adotem procedimentos de pesquisa qualitativa, de caráter indutivo, possa contribuir para a obtenção de informações mais detalhadas e aprofundadas a respeito da percepção dos sujeitos, servindo para identificar itinerários pessoais de aprendizagem, muito úteis para um processo de avaliação e reestruturação pedagógica e curricular, na formação do professor.…”
unclassified
“…In a similar study on PE teacher candidates made by Zach et al (2012), all scores related to professional competence in the field of teaching, in general, and in PE teaching, in particular, were observed to increase after the third year of license education. Moreover, it was emphasized that while teacher education programs alone cannot increase teaching competence in one year, the education to be received in the first three years can increase teaching competence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both PE teachers' insufficient knowledge and underdeveloped teaching skills are reported to affect their willingness to teach (Martin et al, 2008;Siedentop 2002;Tsangaridou 2002). Another striking point regarding the self-efficacy studies conducted in the PE field is the fact that most studies in the literature have concentrated on experienced teachers and that there have only been a limited number of studies conducted on teacher candidates' self-efficacy levels and perceptions (Zach, Harari, & Harari, 2012).…”
mentioning
confidence: 99%
“…According to Zach, Harari and Harari (2012), PST's efficacy beliefs have not been widely considered. However, these authors also reported that a study by Gurvitch and Metzler (2009) found that practicum experience and teacher education programs also have an important effect on establishing PST efficacy beliefs.…”
Section: The Theorymentioning
confidence: 99%